OPTIMIZATION OF WORKING PROCESSES OF INTERNAL COMBUSTION ENGINES WITH THE PURPOSE OF IMPROVING THEIR ENVIRONMENTALITY - Розум, Руслан; Шевчук, Оксана; Прогній, Павло (Modern engineering and innovative technologies, 2022)
The analysis of the factors influencing ecological and economic indicators of work of automobile internal combustion engines is carried out in the work. The current state of the automotive market and the share of cars equipped with internal combustion eng